Hubungan Status Gizi dan Aktivitas Fisik dengan Kejadian Hipertensi Remaja - Saputri, Romadhiyana Kisno; Al-Bari, Akhmad; Pitaloka, Ria Indah Kusuma (Jurnal Gizi, 2021)
Adolescence is peak height velocity that affect changes in body composition, rapid growth on weight, bone mass, pysical activity and nutritional status. Overweight and lack of physical activity are risk factors of hyertension in adolescents. Overweight adolescents have a 4,85 times risk of developig hypertension compared to adolescents with normal nutritional status. Lack of physical activity has 7,86 times the risk of developing hypertension than adolescents with active physical activity. Hypertension in adolescents increase risk of morbidity and mortality in adults.This study aim to determine the correlation between nutritional status and physical activity with hypertension in adolescents. A quantitative research with cross sectional design was developed. Respondents in this study were 75 college students. Data analysis using Spearman’s Correlation test.Proportion of obesity and overweight was 20%. Physical activity of the respondents belongs to light category. The incidence of hypertension I 14,67% and hypertension II 2,67%. Results shows that there was correlation between nutritional status and physical activity with hypertension in adolescents.Keywords :  nutritional status, physical activity, hypertension, adolescents